Analysis of Financial Performance By Using The CAMEL Method In Banking Companies Index LQ45 Period 2018-2022 - Ika Nazilatu Rohmah; Nur Rohmansah (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to determine financial performance using the CAMEL method in LQ45 Index banking companies for the 2018-2022 period. The sample in this research is the financial reports of LQ45 index banking companies for the 2018-2022 period. The type of data used is secondary data. Data collection was carried out using the documentation method, the data source used was taken from the official website of the Indonesian Stock Exchange. The result show that Capital Adequacy Ratio (CAR) calculations for LQ45 index banking companies for 2018-2022,  is in a Very Healthy condition. Non Performing Loan (NPL) calculations for LQ45 index banking companies for 2018-2022,  is in a healthy condition. Net Interest Margin (NIM) calculations,  is in a Very Healthy condition. Return On Assets (ROA) calculations for LQ45 index banking companies for 2018-2022, is in a very healthy condition. Operational Costs and Operating Income (BOPO) for LQ45 index banking companies for 2018-2022,  is in a Very Healthy condition. Loan Deposit Ratio (LDR) calculation for LQ45 index banking companies for 2018-2022, is in a fairly healthy condition